The dialectics of religion and power: Political communication of NU and Muhammadiyah elites in local electoral politics - Turhamun; Siti Nurmahyati (UIN Kiai Haji Achmad Siddiq Jember, 2026)
Religious organizations occupy a contested position in electoral democracy because institutional neutrality can coexist with communication with political actors. Drawing on Habermas’s distinction between communicative and strategic action, this study examines how Nahdlatul Ulama (NU) and Muhammadiyah elites negotiated neutrality, religious authority, and political engagement during the 2024 General Election and Regional Head Election in Banyumas Regency. Using a qualitative case study, data were collected from October 2024 to February 2025 through eight semi-structured interview sessions with nine participants, non-participant observation, and documentary analysis. Data were analyzed through data condensation, data display, and conclusion drawing, using communicative and strategic action as analytical categories. The findings show that both organizations avoid partisan endorsement while continuing to communicate with candidates, legislators, and local officials. NU relied on Kiai, pesantren, religious forums, and culturally embedded relations, whereas Muhammadiyah emphasized organizational structures, public-service institutions, and policy advocacy. Political education, dialogue, and the articulation of aspirations coexisted with legitimacy seeking, institutional networking, and policy access. This coexistence is conceptualized as a dual communicative mode. The study concludes that organizational neutrality regulates rather than eliminates political influence, while transparency, equal access, and clear boundaries between public advocacy and electoral endorsement are necessary to preserve democratic legitimacy.